The Influence of Income and Community Trust on the Decision to Donate Cash at the Ruhul Mukminin Mosque, Musi Rawas Regency - Arinda Purwaningtia; Lemiyana; Chici Rima Putri Pratama (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
This research aims to analyze the influence of income and community trust on the decision to donate cash at the Ruhul Mukminin Mosque, Musi Rawas Regency.The method used in this research is a quantitative approach. The sample used was 85 respondents from a population of 561 people. The technique for using the sample was systematic purposive sampling. With primary data sources using the IBM SPSS Statistics 29 tool. The results of the research that has been conducted show (1) for the t-test results, the calculated t value > t table (3,622 > 1,990) means that income influences the decision to waqf money (2) for the t-test results, the calculated t value > t table (3,487 > 1,990) means that public trust influences the decision to waqf money (3) for the f-test results, the calculated f value > f table (22,087 > 3.11) means that simultaneously income and public trust influence the decision to waqf money. And the coefficient of determination (R Square) is 0.592, which means that income and public trust have an influence on the decision to waqf money of 52.9%.